Tari Semut Karya Arif Rofiq dan Budi Alfan Sebagai Sarana Edukasi Anak (Jurnal Sitakara, 2023)
The reseach aims to discuss of  the ant dance. The problem of this research can be formulated as follows: how the ant danceworks and how the ant dance educates children. The purpose of this study is to describe the form of the ant dance and how to explain and how to educate children. The literati use theory of Slamet Md to reveal the element of ant dance namely: motion, rhythm or accompaniment, expression or taste, costumes, stage venues, and dancers. Educational theory by John Locke is ta bula rasa. The ant dance imitates the movement of the ant animal, by using Desmond Morries' theory, namely theatrical mimicry, imitates the actual motion. The metode that i have used is qualitative, data collection techniques using observation, interviews, and literature study. The results of this study, the ant dance is a choreography in the form of a group, can be danced by six dancers aged 4-11 years wearing a costum which is visualizes  the  ant.  The  motions  composed  by the  choreographer  are  imitative motions of ant animals. The musical is contained and adapted to the characteristics of the children, namely music that describes an atmosphere of joy and agility. Ant dance as a means of education which is realized in the form of imitative movements that are embellished with children's playing movements. Ant Dance help children to developed motoric sytem, kognitif system, social-emosion system, and developed their linguistic’s ability.Keywords: Ant Dance, form, and education.